The Papers of Jefferson Davis : 1871-1879 - Parrish, T. Michael; Gibbs, Suzanne Scott; Crist, Lynda Lasswell (Book collections on Project MUSE., 2012)
Volume 13 of The Papers of Jefferson Davis follows the former president of the Confederacy as he becomes head of the Carolina Life Insurance Company of Memphis and attempts to gain a financial foothold for his newly reunited family. Having lost everything in the Civil War and spent two years immediately afterwards in federal prison, Davis faced a mounting array of financial woes, health problems, and family illnesses and tragedies in the 1870s. Despite setbacks during this decade, Davis also began a quest to rehabilitate his image and protect his historical legacy.